2018
DOI: 10.1186/s12936-018-2427-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caregivers’ consistency of use of bed nets in Nigeria: a multilevel multinomial analysis of survey data

Abstract: BackgroundMalaria remains endemic in Nigeria despite programmes and policies put in place toward malaria elimination. Long-lasting insecticidal nets have been documented to offer protection from malaria by preventing mosquito bites. While many studies have examined the factors associated with the use of bed nets in Nigeria and across Africa, little information is available on the factors associated with consistency of use of bed nets.MethodsThe data for this study were derived from a household survey conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 36 publications
15
48
1
Order By: Relevance
“…Since 2011, about 24 million nets have been provided free of charge in the country [9]. Despite these efforts at promoting net use and the resources committed to the programme, less than half of the women in the country use mosquito nets [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2011, about 24 million nets have been provided free of charge in the country [9]. Despite these efforts at promoting net use and the resources committed to the programme, less than half of the women in the country use mosquito nets [10].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made by researchers to examine the factors influencing mosquito net use among women or caregivers that possessed mosquito nets. Some of the factors attributed to this include age, education, household wealth [11][12][13], household size, distance to health facility, ideational factors [10,14,15], knowledge about efficacy of mosquito nets to prevent malaria, source of knowledge of mosquito nets and socioeconomic class [16,17]. Only few of these studies considered the effects of contextual factors on mosquito net use.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported IRS refusal and failing to remove stagnant water bodies (Ingabire et al, 2015;Kaufman et al, 2012;Munguambe et al, 2011). From these studies, there are indications that the use of malaria preventive measures is partly determined by the perception of the risk of malaria infection and the effectiveness of these measures, by the increased prevalence of insects in the house after spraying, and by throwing LLINs away once they become dirty or torn out (Babalola et al, 2018;Birhanu et al, 2015;Hung et al, 2014;Ingabire et al, 2015;Kaufman et al, 2012;Munguambe et al, 2011;Watanabe et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Only few studies assessed the determinants of consistent bed net use (Babalola et al, 2018;Koenker et al, 2013), and as of yet, there is no evidence of the extent to which the identified determinants affect the intentions to use malaria preventive measures consistently, how important they are and how they can be influenced. In addition, a study using an integrated model of determinants of malaria preventive behaviour that maps the association between these perceptions and intentions to use these preventive measures is lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation